Improved, scalable techniques to cultivate fire mosses for rehabilitation. (16th July 2019) - Grover, Henry S.; Bowker, Matthew A.; Fulé, Peter Z.
Abstract : As wildfires increase in extent and severity in the western United States, land managers need new tools to stabilize and rehabilitate impacted hillslopes. One potential tool is the use of three disturbance‐adapted mosses Ceratodon purpureus (Redshank), Funaria hygrometrica (Cord moss), and Bryum argenteum (Silvergreen moss), collectively known as fire mosses. By growing and adding vegetative propagules in the form of gametophyte fragments to burned hillslopes, land managers could potentially increase the rate of moss colonization and stabilize soils. A first step in developing a native plant materials rehabilitation technique is overcoming propagule limitations using ex situ cultivation. We focused on greenhouse cultivation of moss gametophyte fragments allowing us to grow vegetative propagules with control over atmospheric, edaphic, and hydrologic conditions. In this experiment, we grew fire mosses using an easily scalable technique and commercially available materials. We demonstrated repeated success growing these species in the greenhouse and fine‐tuned harvesting techniques to increase productivity. We found that fire moss achieved high cover in 2 months when grown on organic substrate with constant wicking hydration and a protective shade covering, but growth was not favored by addition of burned materials. We successfully upscaled our growing technique, and developed efficient harvest methods. This success overcomes an initial barrier to testing and developing fire mosses as a novel rehabilitation technique.